Public healthcare resource allocation and the Rule of Rescue. Issue 7 (30th June 2008) - Cookson, R; McCabe, C; Tsuchiya, A
Abstract : In healthcare, a tension sometimes arises between the injunction to do as much good as possible with scarce resources and the injunction to rescue identifiable individuals in immediate peril, regardless of cost (the "Rule of Rescue"). This tension can generate serious ethical and political difficulties for public policy makers faced with making explicit decisions about the public funding of controversial health technologies, such as costly new cancer drugs. In this paper we explore the appropriate role of the Rule of Rescue in public resource allocation decisions by health technology funding advisory bodies such as the National Institute for Health and Clinical Excellence. We consider practical approaches to operationalising the Rule of Rescue from Australia and the UK before examining the relevance of individual moral imperatives to public policy making. We conclude that that whilst public policy makers in a humane society should facilitate exceptional departures from a cost effectiveness norm in clinical decisions about identified individuals, it is not so obvious that they should, as a matter of national public policy, exempt any one group of unidentified individuals within society from the rules of opportunity cost at the expense of all others.